TABALONG RIVER FLOOD CONTROL AT TABALONG DISTRICT SOUTH KALIMANTAN - Dodi Hartoni Unjang (Jurnal Teknologi Berkelanjutan, 2014)
Tabalong district has a fairly big river that is Sungai Tabalong. It often overflows during the rainy season and floods residential areas, agriculture area, erosion of the river bank and the neighboring road next to the river. This study aims at investigating the problem by determining the flood discharge, the water surface profile as well as the flood control, such it will then be used to determine how best to control the flood. Flood discharge obtained from the transformation of rainfall data and flood discharge hydrograph using Synthetic Unit Hydrograph Method by Nakayasu, hydraulics analysis to obtain the flow profile using the standard step method with the aided of a computer program HEC - RAS 4.1.0. The results showed that the maximum discharge obtained with Synthetic Unit Hydrograph Nakayasu each return period Q2years = 2913.93 m3/s, Q5years = 3626.02 m3/s, Q10years = 4097.48 m3/s, Q25years = 4771,33 m3/s, Q50years = 5307.70 m3/s, Q100years = 5871.43 m3/s, the analysis of unsteady flow hydraulics with flow simulation found that on 50 years return period flooding occurred in Sungai Tabalong in Sta. 0 to Sta. 25. It is found that the flood can be controlled by normalizing the river channel, by using embankment (levees) on the left and right side of the river, or through diversion.